An oxygen tolerance conductive hydrogel anode membrane for use in a potentially implantable glucose fuel cell. Issue 114 (30th November 2016) - Liu, Shumin; Zheng, Yudong; Sun, Yi; Su, Lei; Yue, Lina; Wang, YanSen; Feng, Jingxuan; Fan, Jinsheng
Abstract : Schematic of the PtNPs/MWCNTs/BC anode membrane. Abstract : Since glucose and oxygen are simultaneously present in body fluids, the electrode reactions at the anode are required to avoid mixed electrode potentials in implantable glucose fuel cells. Based on the different concentrations of glucose and oxygen in body fluids, we took advantage of the catalytic activity of platinum nanoparticles, the current collector of the multiwalled carbon nanotubes and the diffusion restriction of the bacterial cellulose to design a conductive hydrogel electrode membrane, in which the electrode reactions of the anode are dominated by glucose oxidation in an oxygen-rich phosphate buffer solution. The conductive hydrogel electrode membrane was prepared through a combined approach involving electrophoretic deposition treatment and in situ synthesis. The fabricated membrane had a laminated structure with three-dimensional nanopores, with a structure resembling a RANEY®-type platinum, albeit the conductive hydrogel electrode membrane had the higher oxygen tolerance than the RANEY®-type platinum. We utilized the conductive hydrogel electrode membrane as the anode and a platinum sheet as the cathode to build a single compartment implantable glucose fuel cell. Even in the case of the platinum sheet cathode, having very limited catalytic activity, the performance of the fuel cell was close to the implantable RANEY®-type platinum fuel cell. In particular, the conductive hydrogel electrode membrane had the same excellent biocompatibility as that of the bacterial cellulose.